Analisis Prediksi Prestasi Siswa UPTD SD Negeri 30 Aek Batu Dalam Machine Learning Dengan Metode Naive Bayes - Mira Nanda Ambarita; Marnis Nasution; Rahma Muti Ah (Jurnal Informatika, 2024)
Education is one of the efforts made to determine the success of a nation, successful education will continue to produce a good generation as well. Along with the rapid global challenges, the challenges of the world of education are becoming greater, this aspect that encourages learners to achieve the best achievements. Given the presence of teachers in the process of teaching and learning activities is very influential, it should be the quality of teachers must be considered. The problem that often occurs in every school, especially in UPTD SD Negeri 30 AEK Batu, is that there are many students who are lazy to learn, students who lack fun lessons, do not have attention to what has been learned, school assignments are a burden, learning outcomes are only to go to class or graduate from school and school just to meet friends and get pocket money. Therefore, to predict the achievements of different students, the education of UPTD SD Negeri 30 AEK Batu requires accurate data on student achievement so that it can be a reference for education to better know the achievements of students who excel and underachieve.  Application of student achievement prediction UPTD SD Negeri 30 AEK Batu in machine learning with naive bayes method can be solved well or not.